KAJIAN KERENTANAN PENGHIDUPAN PEMBUDIDAYA IKAN KARAMBA BAMBU DI SUNGAI WIDURI, KASIHAN, BANTUL - Triwijayani, Ade Utari; Auliatun Nissa, Zulfa Nur (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2025)
The study on the livelihood vulnerability of bamboo fish farmers in the Widuri River, Kasihan, Bantul, is essential for understanding the factors influencing their resilience to environmental risks. This research employs a quantitative method with a census approach, involving ten respondents who are bamboo fish farmers in the area. The collected data includes demographic profiles, education levels, farming experience, and aspects related to vulnerability, such as environmental pressure, adaptive capacity, and sensitivity. The analysis results show that the majority of respondents have a high school education, and most have less than one year of farming experience, indicating a significant interest among newcomers in fish farming activities. The farmers are vulnerable, with a Livelihood Vulnerability Index (LVI) score of 0.59. The pressures faced, such as floods and pollution, significantly impact their enterprises. An adaptive capacity score of 0.70 indicates a need for skill enhancement and income diversification. Additionally, their high dependence on fish farming as the primary source of income increases their vulnerability. Based on these findings, it is recommended that interventions be made through training in farming techniques, product diversification, and strengthening social networks to improve the adaptive capacity and resilience of farmers in facing existing environmental challenges. This research contributes significantly to developing risk mitigation strategies and the sustainability of fish farming enterprises in the region.